On a model of enterprise architecture for public institutions in Romania - Cristian Bologa; José Luis Vázquez; Gheorghe Faur; Paul Bresfelean; Nicolae Ghisoiu (Responsibility and Sustainability, 2013)
This paper presents a possibility to conceive the conceptual design of a Romanian public institution using a methodology known as the “Enterprise Architecture”. The Enterprise Architecture will be applied to any public institution, regardless of hierarchical level in the overall organizational structure. This Architecture can be divided into four components: Business Architecture, Information Architecture, Software Architecture and Technological Architecture.